Kom ons stem: Wat het Jesus regtig gesê? - Botha, J. (Hervormde teologiese studies, 1990)
Let us vote: What did Jesus really say? Since 1985 the study of the Jesus tradition has taken interesting new directions in the USA. A Jesus Seminar was initiated by the well-known RW Funk and some other leading American New Testament scholars. The question of what Jesus himself really said and what was attributed to him by tradition during later stages, was tackled anew with the explicit additional aim of ‘popularizing’ the results of this research. Since its inception the Jesus Seminar has grown into an academic institute, Westar Institute, with a whole range of research activities. In addition to this, a new publishing house for biblical and related subjects, Polebridge Press, was launched. In this article all these developments are discussed, with special attention to the Jesus Seminar. Finally, by applying the philosophical concepts of ‘exigence’ and ‘rhetorical situation, the article gives a possible ‘explanation’ for these new stimuli in some circles of American biblical scholarship.